The Argument of Kampung Tangguh Pancasila as a Process of Strengthening Pancasila as Living Values (a respect note to The late Prof. Dr. Hermanu Joebagio, M.Pd.) - Haryani Saptaningtyas; Akhmad Ramdhon; Ardeti Jeni Abdilla (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
This paper is a respect note as well as an afterthought on the ideas of The late Prof. Dr. Hermanu Joebagio, M.Pd. about Pancasila as Living Values and how it was conceptualized as the design of the Kampung Tangguh Pancasila program. Kampung Tanggung Pancasila is a work to present the campus as an academic space and a space for community service as well as a bottom-up approach process that explores the values of Pancasila that were practiced by the community.